THE HEMATOPOIETIC GROWTH FACTORS – A NEW PERSPECTIVE IN THE NEUROPROTECTIVE THERAPY OF THE ISCHEMIC STROKE - Dana Fodor (Romanian Journal of Neurology, 2009)
The hematopoietic growth factors (HGF) have been known for 20 years, named for their role in the proliferation, differentiation and survival of hematopoietic progenitor cells. They (erythropoietin, G-CSF and GM-CSF) have been used many years in clinical practice in oncological and hematological pathology. Recent studies suggest that HGF have also important non-hematopoietic functions in the central nervous system. HGF and their receptors are expressed by neurons in many brain regions and are up-regulated after focal ischemia, indicating an autocrin protective response of the injured brain. The neuroprotective function of HGF has been suggested by the effect of decreasing infarct volumes in different experimental models in rodents and has been attributed to their anti-apoptotic activity (by activating several protective pathways, PI3K/Akt being the most important). Moreover, HGF induces neurogenesis and angiogenesis, possible the substrate of improving recovery post-stroke. There is emerging data from recent studies suggesting that EPO, G-CSF and GM-CSF are potential new agents, a novel type of multifactorial drugs and candidates for neuroprotection in ischemic stroke. Here we discuss this new property of HGF behind the known function in hematopoietic system, summarize data from literature concerning HGF’s actions in cerebral ischemia and highlight clinical implications.